Effect of day time climatic conditions associated with different 2, 4-D formulations on spray deposition and weed control. Issue 10 (3rd October 2019) - Contiero, Robinson L.; Rios, Fabiano A.; Biffe, Denis F.; Braz, Guilherme B. P.; Constantin, Jamil; de Oliveira, Rubem S.; Gheno, Eliezer A.; Lucio, Felipe R.
Abstract: The aim of this study was to evaluate the effect of time of the day and their associated climatic conditions on spray deposition of two 2, 4-D formulations, as well as the influence on weed control. The experiment was installed in the field in complete randomized design. Treatments were arranged in factorial design 8 × 2, with 20 repetitions. First factor corresponded to different application time (1:00, 4:00, 7:00, 10:00, 13:00, 16:00, 19:00, and 22:00) with their respective climatic conditions. The second factor consisted of two formulations of 2, 4-D applied at 776 g a.e. ha −1 (2, 4-D amine and 2, 4-D choline salt with Colex-D™ Technology) + glyphosate (816 g a.e. ha −1 ). There was more spray deposition when 2, 4-D choline formulation was used, and such differences were more evident for applications performed under adverse climatic conditions. More spray deposition was found in applications performed at times of day with more favorable temperature and humidity of the air conditions. Only the initial control of the evaluated species was affected by the time of application.